Persepsi Siswa pada Program Makanan Bergizi Gratis terhadap Konsentrasi Belajar Siswa di SMP Negeri 8 Gorontalo - Mohamad Emil Dunggio; Zulaecha Ngiu; Yuli Adhani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Quality education is influenced by various factors, one of which is the fulfillment of students’ nutritional needs related to learning readiness and concentration. The Free Nutritious Meal Program is a policy aimed at improving students’ nutritional status while supporting the learning process at school. This study aims to analyze students’ perceptions of the Free Nutritious Meal Program and its implications for students’ learning concentration at SMP Negeri 8 Gorontalo. The study employed a qualitative approach with a case study design. The research informants consisted of students as the main informants, as well as teachers and school administrators as supporting informants selected purposively. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model through the stages of data reduction, data display, and conclusion drawing. The results showed that most students had positive perceptions of the program because it helped reduce hunger during lessons, increased enthusiasm for attending classes, and reduced daily expenses. In addition, the program was considered to contribute to improved focus, classroom participation, and learning endurance during school hours. However, several obstacles were still found, including limited menu variety and meal distribution timing that needs improvement. The implications of this study indicate that fulfilling nutritional needs through school programs can be an effective strategy to improve the quality of learning, therefore continuous evaluation is needed to enhance the implementation of the program.